GAMBARAN PENGGUNAAN METODE PROBLEM SOLVING OLEH GURU DALAM PEMBELAJARAN DI SMK BINA BHAKTI CILACAP - Lusiani Lusiani; Andi Hendrawan; Fajar Firmansyah; Supriyanto Supriyanto (KOLONI, 2022)
The teacher acts as a facilitator so that learning objectives can be achieved. This can be done using the problem solving method, so the authors are interested in providing an overview of the use of problem solving by teachers in learning at SMK Bina Bhakti Cilacap. This study uses qualitative research methods through descriptive and quantitative approaches. The location is located at the Bina Bhakti Cilacap Vocational School offline with the subject teacher at the school. It is concluded that the use of problem solving is quite well achieved in accordance with the four steps/stages that must be carried out so that learning can be achieved optimally. Keywords: teacher, problem solving, learning